THE MODERN TEACHER AS A SUBJECT IN THE PROCESS OF FORMING FUTURE PHD`S CULTURE OF ACADEMIC INTEGRITY: TEMPORA MUTANTUR, ET NOS MUTAMUR IN ILLIS - Kuzmenko, Anastasiia (Periodyk Naukowy Akademii Polonijnej, 2024)
The article is aimed to characterize the skills and qualities of a modern university teacher in Ukrainian higher education as a subject in the process of forming the culture of academic integrity for the future Doctor of Philosophy. The instructor must showcase a profound grasp of the various scientific fields they teach, possessing the foundational knowledge to tackle diverse socio-economic, production, and cultural challenges. Furthermore, it is crucial for the instructor to remain abreast of new research, discoveries, and hypotheses, anticipating the evolving landscape of the science they teach and fostering a culture of scientific and pedagogical thought. Effective communication skills are essential for instructors, facilitating lucid and accessible explanations of intricate concepts and enhancing students’ comprehension of the material. The instructor’s capacity to stimulate the intellectual growth of PhD candidates, nurture creative and critical thinking, and employ innovative teaching methodologies delineates a high level of professionalism. An instructor should also be committed to encouraging the personal development of students, fostering their critical thinking, creative autonomy, and self-expression. All these efforts contribute to the cultivation of academic integrity among PhD candidates. In essence, these characteristics converge to transform the instructor into not just a conduit of knowledge but also a mentor who nurtures the scholarly potential of future PhDs.